Is It Useful to Monitor Thiopurine Metabolites in Pediatric Patients with Crohn's Disease on Combination Therapy? A Multicenter Prospective Observational Study - Pospisilova, Kristyna; Siroka, Jitka; Karaskova, Eva; Hradsky, Ondrej; Lerchova, Tereza; Zarubova, Kristyna; Copova, Ivana; Gonsorcikova, Lucie; Velganova-Veghova, Maria; Francova, Irena; Urbanek, Lubor; Geryk, Milos; et al. (Paediatric drugs, 2021)
BACKGROUND: The additional value of azathioprine concomitant treatment on infliximab pharmacokinetics in children is not well described yet. AIMS: In the present study, we aimed to describe the relationship between thiopurine metabolite levels, infliximab trough levels, anti-IFX antibody formation, and clinical and laboratory markers of disease activity in pediatric patients with Crohn's disease, and to assess non-adherence. METHODS: Data were collected prospectively during repeated visits from pediatric patients followed for Crohn's disease in two Czech pediatric inflammatory bowel disease centers between January 2016 and June 2017. Thiopurine metabolites (6-thioguanine and 6-methylmercaptopurine) were measured by high-performance liquid chromatography. Infliximab trough levels and anti-IFX antibody serum levels were measured routinely by ELISA. The risk of loss of response to infliximab therapy was also assessed. RESULTS: A significant association between infliximab serum levels and 6-thioguanine erythrocyte levels was observed when tested as categorical variables (63 patients, 321 observations). To predict infliximab levels > 5 µg/mL, we propose a 6-thioguanine cutoff of 278 pmol/8 × 108 erythrocytes (sensitivity, 0.799; specificity, 0.347). A higher loss-of-response-to-infliximab rate (tested in a subgroup of 51 patients) was observed in patients with undetectable 6-thioguanine levels than in those with detectable levels (p = 0.026). Non-adherence to azathioprine therapy was suspected in 20% of patients. CONCLUSION: Thiopurine metabolite monitoring in pediatric patients with Crohn's disease is useful when optimizing combination therapy. Pediatric patients with undetectable 6-thioguanine levels are more likely to lose response to infliximab therapy. When targeting optimal infliximab levels, the 6-thioguanine cutoff levels in children appear to be higher than in adults.
Keywords: Infliximab; infliximab; Female; azathioprin; dítě; biologické markery; Biomarkers; ženské pohlaví; longitudinální studie; Adolescent; imunologické faktory; lidé; Mercaptopurine; Azathioprine; Crohn Disease; prospektivní studie; Immunologic Factors; Male; Prospective Studies; kombinovaná farmakoterapie; Child; Crohnova nemoc; mužské pohlaví; merkaptopurin; mladiství; Longitudinal Studies; Drug Therapy, Combination; Humans